G436(P) Using digital methods to stop reinventing the wheel: baseline audit of london asthma standards and creation of the asthma toolkit. (24th May 2017) - Bhatt, R; Nelson, S; Parr, T; Finch, D; Iles, R
Abstract : Aims: Over recent years there have been approximately 16 documents about managing asthma effectively. Despite this we still have the highest mortality and morbidity secondary to asthma in children and young people (CYP) in Europe. Within London exists pockets of good practice in asthma management and yet we are constantly reinventing resources due to lack of joint working. This quality improvement project aims to audit the Healthy London Partnership London asthma standards 1 and build a solution to drive up quality of care provided in the form of an online toolkit aimed at parents and carers, to commissioners and providers across the system. Methods: We undertook a baseline audit against the London asthma standards across 32 CCGs and acute providers. Results were submitted in the form of self-assessed RAG (red, amber green) Rating and in order aimed at helping boroughs to understand what their gaps were. A digital Asthma Toolkit was created to help them implement the standards a digital Asthma Toolkit was created. Results: The baseline audit was completed by 31 clinical commissioning groups and acute providers. The audit showed significant variation in practice with areas such as school and out of hospital care being largely RAG Rated as red. The toolkit created to help drive up standards has had 23 611 page views (1400 unique views) and 811 downloads and over 1200 film views since its launch. It has resulted in a number of additional resources being made available, including new asthma nurse posts. The website and programme allow services to save resource and time e.g. not writing 32 different sets of guidelines. One commissioner commented, 'This resource has saved us five years of work.' Conclusion: Standardising the care that we provide for CYP with asthma will help towards reducing the mortality and morbidity in this vulnerable group. Sharing good practice and resources allows healthcare professionals to learn from each other and maximise scarce NHS resources. Having a toolkit that can be accessed anytime and anywhere allows the first steps in integrating care and bringing the health system together includes CYP, Parents and carers in addition to service providers.